Reasons for human milk donation according to different per capita income - João Antonio Barbosa dos Santos; Vilneide Maria dos Santos Braga Diégues Serva; Maria de Fátima Costa Caminha
Abstract Objectives: to identify the reasons for human milk donation according to different per capita income in donors who were registered in the human milk bank and center to promote breastfeeding at Instituto de Medicina Integral Professor Fernando Figueira (HMB/CIAMA/IMIP). Methods: this is a cross-sectional study. Data collection was carried out at the HMB/CIAMA/IMIP from March to May 2015. The sample was consisted of 155 donors. The data were obtained by applying a form elaborated by the researchers. For the data analysis the SPSS 13.0 software for Windows and Excel 2010 were used. Results: the reasons most mentioned by the donors with a per capita income of < 0.5 minimum wages were, in descending order: excess of milk /avoid wasting, solidarity, altruism and return to work. Donors with a per capita income of ≥ 0.5 minimum wages were, excess of milk /avoid wasting and return to work were the main reasons for donation, followed by solidarity and altruism. Conclusions: the reasons for human milk donation varied according to the per capita income. This knowledge will contribute with the necessary information for planning/improved interventions to capture new donors locally and nation wide.